Preparation of polyhedral oligomeric silsesquioxane based hybrid monoliths by thiol-ene click chemistry for capillary liquid chromatography. Issue 1 (4th November 2014) - Shen, Shufen; Ye, Fanggui; Zhang, Cong; Xiong, Yuhao; Su, Linjing; Zhao, Shulin
Abstract : A facile organic–silica hybrid monolith was prepared by a thiol-ene click reaction of polyhedral oligomeric silsesquioxane methacryl substituted (POSS-MA) with 1, 4-bis(mercaptoacetoxy) butane (BMAB) using toluene and dodecanol as a porogenic system. Abstract : A facile organic–silica hybrid monolith was prepared by a thiol-ene click reaction of polyhedral oligomeric silsesquioxane methacryl substituted (POSS-MA) with 1, 4-bis(mercaptoacetoxy) butane (BMAB) using toluene and dodecanol as a porogenic system. The effects of the ratio of POSS-MA–BMAB and porogenic solvents and click reaction temperature on the morphology, permeability and column performance of the resulting POSS–BMAB hybrid monoliths were studied in detail. A uniform monolithic network with a high porosity was obtained. The POSS–BMAB hybrid monolith exhibited good permeability and high thermal and mechanical stability. A series of test compounds, including alkylbenzenes, polycyclic aromatic hydrocarbon, phenols and, anilines were used to evaluate the retention behaviors of the POSS–BMAB hybrid monolith in capillary liquid chromatography. The prepared POSS–BMAB hybrid monolith exhibited typical reversed-phase chromatographic behavior toward neutral solutes. The minimum plate height of this hybrid monolith was determined as 12.6 and 13.7 μm for thiourea and benzene, respectively. These results demonstrate that thiol-ene click chemistry can provide a facile and robust approach for the preparation of a POSS-based hybrid monolith.